PENGARUH PROFITABILITAS, PRUDENCE, DAN VARIABEL LAINNYA TERHADAP KUALITAS LABA - PRISCILIA DESMITA; ANNISA KANTI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
The objective of this research is to obtain empirical evidences regarding the effect of Company Size, Liquidity, Investment Opportunity Set, Leverage, Profitability, Institutional Ownership, Profit Growth, and Prudence on Earnings Quality. This research was conducted on all manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The sampling method used in this research is purposive sampling, which requires various criteria to obtain the number of samples to be researched. After conducting the sampling process, this research will use 77 companies with a total of 231 data that have passed the criteria. Hypothesis testing used in this research is a multiple linear regression model. The findings reveal that Profitability and Prudence impact on earnings quality. However, Company Size, Liquidity, Investment Opportunity Set, Leverage, Institutional Ownership, and Profit Growth show no effect on earnings quality.